Changes in Biochemical Characteristics and Activities of Ripening Associated Enzymes in Mango Fruit during the Storage at Different Temperatures - Hossain, M.A; Rana, M.M; Kimura, Y.; Roslan, H.A (Hindawi Publishing Corporation, 2014)
As a part of the study to explore the possible strategy for enhancing the shelf life of mango fruits, we investigated the changes in biochemical parameters and activities of ripening associated enzymes of Ashwina hybridmangoes at 4-day regular intervals during storage at −10∘C, 4∘C, and 30 ± 1 ∘C. Titratable acidity, vitamin C, starch content, and reducing sugar were higher at unripe state and gradually decreased with the increasing of storage time at all storage temperatures while phenol content, total soluble solid, total sugar, and nonreducing sugar contents gradually increased. The activities of amylase,